STRATEGY FOR IMPLEMENTING CIRCULAR ECONOMY IN WASTE MANAGEMENT IN THE COASTAL AREA OF LHOKNGA DISTRICT, ACEH BESAR REGENCY - Rahima, Ghefira; Fathma, Syarifah Seicha (Center for Environmental Studies, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Waste management in the coastal area of Lhoknga District Aceh Besar Regency, still faces various challenges, both technical and non-technical. Waste is generally disposed of without segregation, openly burned, or directly discharged into the environment without adequate treatment. This study aims to analyze the existing conditions of solid waste management, map material flows within the waste management system, and formulate strategies for implementing a circular economy approach using SWOT analysis. The methods employed include field observations, waste generation measurements, and in-depth interviews with local residents. The results indicate that household activities are the dominant source of waste generation, with the largest composition consisting of organic waste, particularly coconut waste with a generation rate of 0.061 kg/person/day and food waste amounting to 0.072 kg/person/day. The application of the 9R principles by the community remains limited and is primarily confined to reuse, recycle, and recovery practices. Based on the SWOT analysis, the waste management strategy is positioned in Quadrant I, indicating a favorable condition characterized by strong internal capacities and significant external opportunities. The recommended strategies emphasize an aggressive growth approach through the establishment of Waste Collecting Points (WCPs), the development of educational tourism initiatives, and the strengthening of local partnerships. This approach integrates material flow analysis with strategic assessment at the local level and is expected to support sustainable coastal waste management based on circular economy principles.